Comparative evaluation of Color stability of indigenously developed bioceramic Ceremagnum plus with MTA in distilled water and hypochlorite solution - Mitra, Anusua; Karobari, Mohamed Isaqali (Journal of Neonatal Surgery, 2025)
Background: Tooth discoloration caused by endodontic repair materials is a major clinical concern, particularly in esthetically sensitive regions. Mineral Trioxide Aggregate (MTA), although widely used for its biocompatibility and sealing properties, is associated with significant discoloration, especially in the presence of sodium hypochlorite. Ceremagnum Plus, an indigenously developed calcium silicate–based bioceramic, has been proposed as an alternative with improved optical stability. Aim: This study aimed to compare the short-term color stability of MTA Angelus and Ceremagnum Plus after immersion in distilled water and sodium hypochlorite. Materials and Methods: Standardized cylindrical specimens of MTA Angelus and Ceremagnum Plus were prepared and cured under controlled conditions. Samples were immersed in distilled water and sodium hypochlorite for 24 hours. Color changes (ΔE) were assessed using a spectrophotometer based on the CIE Lab* color system. Statistical analysis was performed using an unpaired t-test, with the level of significance set at P < 0.05. Results: Both materials exhibited discoloration after immersion, with sodium hypochlorite producing greater changes than distilled water. MTA Angelus showed significantly higher ΔE values compared to Ceremagnum Plus in both media (distilled water: 3.96 ± 0.29 vs. 1.39 ± 0.70; sodium hypochlorite: 6.08 vs. 3.01). Ceremagnum Plus consistently demonstrated lower mean color changes, remaining below the clinically acceptable threshold in distilled water and near the threshold in sodium hypochlorite. Conclusion: Ceremagnum Plus exhibited superior color stability compared to MTA Angelus in both distilled water and sodium hypochlorite. Its reduced discoloration potential suggests that it may be a more suitable material for use in esthetically critical regions, where long-term appearance is paramount.